Composite positive electrode material and preparation method and application thereof
By using composite positive electrode materials in the positive electrode materials of the aqueous zinc ion battery, using titanium nitride coating layer and doping element M to enhance the stability and conductivity of the material, the problems of few types and toxicity limitations of existing positive electrode materials are solved, and the problem of Higher cycle stability and battery performance.
Patent Information
- Application Number
- CN202411601742.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
There are fewer types of positive electrode materials for existing water-based zinc ion batteries, especially vanadium oxide materials, due to intrinsic toxicity limitations, and it is difficult to produce and use on a large scale.
Using composite positive electrode material, the material consists of a positive electrode matrix and a titanium nitride coating layer. The positive electrode matrix includes lithium manganese iron phosphate material and dopant element M. The titanium nitride coating layer can slow down Mn dissolution in lithium manganese iron phosphate material .
Through the coordination of doping element M and the carbon material layer, the stability and conductivity of lithium manganese iron phosphate material are improved, and the titanium nitride cladding further enhances the cycle stability and improves the energy density and voltage window of the battery.
Smart Images

Figure CN119447251A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a composite positive electrode material and a preparation method and application thereof. Background Art
[0002] At present, lithium-ion batteries (LIBs) are widely used in the new energy market, such as electric vehicles, power tools, and scene energy storage. Lithium-ion batteries have a high voltage window and energy density. However, lithium battery electrolytes are flammable organic solvents. When safety accidents occur, thermal runaway is prone to occur. Recently, there have been frequent reports of spontaneous combustion of electric vehicles and energy storage boxes. Therefore, high-safety energy storage systems are receiving more and more attention. Aqueous zinc-ion batteries rely on the ultra-high safety of aqueous electrolyte systems. Aqueous batteries use water as a solvent. Compared with non-aqueous systems, aqueous batteries have the characteristics of low volatility, non-toxicity, and non-flammability. At the same time, aqueous electrolytes have high ionic conductivity, and assembly does not require a dry environment. They have unique advantages such as high power, fast charging, and low manufacturing cost. The ultra-low raw material cost and good service life of metallic zinc are gradually becoming a research hotspot in the current large-scale energy storage field.
[0003] The negative electrode material of traditional lithium-ion batteries is usually graphite, and the positive electrode is composed of lithium-containing transition metal oxides. During charging, lithium ions are released from the positive electrode and intercalated into the graphite negative electrode interlayer through the electrolyte, thereby converting electrical energy into chemical energy; during the discharge process, lithium ions are released from the graphite negative electrode and return to the positive electrode, converting chemical energy into electrical energy. Unlike LIBs, traditional aqueous zinc-ion batteries use vanadium oxide as the positive electrode material and zinc metal as the negative electrode to deposit zinc ions. During discharge, zinc ions are stripped from the surface of metallic zinc and undergo a reduction reaction on the positive electrode to form zinc-vanadium oxide. During charging, the reaction path is reversed, and zinc ions will be released from the positive electrode and deposited on the metallic zinc sheet. However, there are currently relatively few types of positive electrode materials for aqueous zinc-ion batteries, especially vanadium oxide materials, which are difficult to produce and use on a large scale in industrial production due to certain limitations in intrinsic toxicity.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One object of the present invention is to provide a composite positive electrode material, wherein the titanium nitride coating layer can slow down the dissolution of Mn in the lithium manganese iron phosphate material, and cooperate with the positive electrode matrix to improve the cycle stability.
[0006] Another object of the present invention is to provide a method for preparing the composite positive electrode material, which is simple and easy to implement, and the obtained composite positive electrode material has good cycle stability.
[0007] Another object of the present invention is to provide a positive electrode sheet.
[0008] Another object of the present invention is to provide an aqueous zinc ion battery.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] A composite positive electrode material comprises a positive electrode substrate and a coating layer coated on the surface of the positive electrode substrate, wherein the positive electrode substrate comprises a core material and a carbon material layer coated on the surface of the core material, the core material comprises a lithium manganese iron phosphate material and a doping element M, the doping element M comprises at least one of vanadium, titanium, niobium and magnesium, and the coating layer comprises titanium nitride.
[0011] In some embodiments, the mass of the coating layer is 2% to 20% of the mass of the composite positive electrode material.
[0012] The method for preparing the composite positive electrode material as described above comprises the following steps:
[0013] Anhydrous manganese ferrophosphate, a lithium source, a carbon source, a dopant containing element M and a solvent are mixed and ground to obtain a first material; a dispersion of titanium nitride and the first material are mixed and stirred, and then dried and calcined.
[0014] In some embodiments, the mass ratio of the anhydrous manganese ferrophosphate, the lithium source, the carbon source, the dopant containing the element M and the solvent is (300-600):(200-350):(120-200):(4-8):(1800-2500).
[0015] In some embodiments, the carbon source includes at least one of starch, sucrose, fructose, maltose, cyclodextrin, citric acid and polyol materials.
[0016] In some embodiments, the dopant containing the element M includes at least one of ammonium metavanadate, titanium dioxide, ammonium metavanadate, vanadium pentoxide, niobium pentoxide, anhydrous magnesium acetate, and magnesium oxide.
[0017] In some embodiments, the lithium source includes lithium phosphate.
[0018] In some embodiments, the anhydrous manganous ferrophosphate is obtained by subjecting a manganous phosphate precursor to heat treatment; the heat treatment temperature is 500 to 600° C., and the heat treatment time is 4 to 6 hours.
[0019] In some embodiments, the rotation speed of the mixing process is 200 to 600 rpm, and the mixing process time is 10 to 30 minutes.
[0020] In some implementations, the mass of the titanium nitride is 1% to 30% of the mass of the first material.
[0021] In some embodiments, the solid content of titanium nitride in the titanium nitride dispersion is 5% to 30%.
[0022] In some embodiments, the preparation of the titanium nitride dispersion specifically includes: subjecting a mixture of titanium nitride and water to high-pressure microfluidization treatment; the pressure of the high-pressure microfluidization treatment is 10,000 to 22,000 psi, the flow rate of the high-pressure microfluidization treatment is 20 to 250 mL / min, and the time of the high-pressure microfluidization treatment is 30 to 60 min.
[0023] In some implementations, the mixing and stirring speed is 300-600 rpm, and the mixing and stirring time is 30-70 min.
[0024] In some embodiments, the drying is performed by spray drying, the inlet air temperature of the spray drying is 150-250° C., the pressure of the spray drying is 0.1-0.3 MPa, and the feed speed of the spray drying is 10-30 rpm.
[0025] In some embodiments, the calcination includes a first constant temperature treatment and a second constant temperature treatment, the temperature of the first constant temperature treatment is 150-250°C, the first constant temperature treatment time is 3-6 hours, the temperature of the second constant temperature treatment is 300-600°C, and the second constant temperature treatment time is 10-15 hours.
[0026] A positive electrode sheet comprises the composite positive electrode material as described above, or the composite positive electrode material prepared by the method for preparing the composite positive electrode material as described above.
[0027] An aqueous zinc ion battery comprises the positive electrode sheet as described above.
[0028] In some embodiments, the battery further comprises an electrolyte, the electrolyte comprising a soluble zinc salt, a soluble lithium salt and water, the soluble zinc salt comprises ZnSO4·7H2O, the soluble lithium salt comprises Li2SO4, the concentration of the soluble zinc salt is 0.7 to 1.2 mol / L, and the concentration of the soluble lithium is 0.2 to 0.5 mol / L.
[0029] In some embodiments, the process comprises: mixing a soluble zinc salt, a soluble lithium salt and water at a mixing speed of 100 to 300 rpm for 10 to 30 minutes.
[0030] An electrical device comprises the aqueous zinc ion battery as described above.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) In the composite positive electrode material of the present invention, the doping element M in the positive electrode matrix can enhance the stability of the lithium manganese iron phosphate material, the carbon material layer can further improve the conductivity, and the titanium nitride coating layer can slow down the dissolution of Mn in the lithium manganese iron phosphate material. Through the coordination of each layer, the cycle stability can be improved.
[0033] (2) The preparation method of the composite positive electrode material of the present invention is simple and easy, and a composite positive electrode material with stable structure and high capacity can be obtained by combining various steps.
[0034] (3) The battery of the present invention uses a composite positive electrode material and an electrolyte, Li + / Zn 2+ Dual charge carriers give it higher energy density and voltage window. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 This is a scanning electron microscope image of the composite positive electrode material of the present invention. DETAILED DESCRIPTION
[0037] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0038] According to one aspect of the present invention, the present invention relates to a composite positive electrode material, including a positive electrode substrate and a coating layer coated on the surface of the positive electrode substrate, the positive electrode substrate includes a core material and a carbon material layer coated on the surface of the core material, the core material includes lithium manganese iron phosphate material and a doping element M, the doping element M includes at least one of vanadium, titanium, niobium and magnesium, and the coating layer includes titanium nitride (TiN).
[0039] In the composite positive electrode material of the present invention, the doping element M in the positive electrode matrix can enhance the stability of the lithium manganese iron phosphate material, the carbon material layer can further improve the conductivity, and the titanium nitride coating layer can slow down the dissolution of Mn in the lithium manganese iron phosphate material. Through the coordination of each layer, the cycle stability can be improved.
[0040] In some embodiments, the lithium manganese iron phosphate material is LiFe 0.4 Mn 0.6 PO4.
[0041] In some embodiments, the mass of the coating layer is 2% to 20% of the mass of the composite positive electrode material, for example 2%, 3%, 5%, 6%, 8%, 10%, 12%, 15%, 18%, 20%, etc. The coating layer of the present invention has a suitable mass, which is more conducive to ensuring the electrochemical properties of the composite positive electrode material.
[0042] In some embodiments, the mass of the doping element M is 0.01% to 0.1% of the mass of the composite positive electrode material, for example, 0.01%, 0.02%, 0.05%, 0.06%, 0.08%, 0.1%, etc.
[0043] According to another aspect of the present invention, the present invention also relates to a method for preparing a composite positive electrode material, comprising the following steps:
[0044] Anhydrous manganese ferrophosphate, a lithium source, a carbon source, a dopant containing element M and a solvent are mixed and ground to obtain a first material; a dispersion of titanium nitride and the first material are mixed and stirred, and then dried and calcined.
[0045] The preparation method of the composite positive electrode material of the present invention is simple and easy, and a composite positive electrode material with stable structure and high capacity can be obtained through the coordination of various steps.
[0046] In some embodiments, the mass ratio of anhydrous manganese ferrophosphate, lithium source, carbon source, dopant containing element M and solvent is (300-600): (200-350): (120-200): (4-8): (1800-2500). For example, 300:200:120:4:1800, 400:250:150:5:1900, 500:300:160:6:2000, 600:200:200:8:2300, etc. The materials of the present invention are used in appropriate ratios, which is more conducive to the reaction.
[0047] In some embodiments, the carbon source includes at least one of starch, sucrose, fructose, maltose, cyclodextrin, citric acid and polyol materials. The carbon source can improve the conductivity of the positive electrode material. The polyol material includes at least one of polyethylene glycol, polyvinyl alcohol and polypropylene glycol. In some embodiments, the carbon source includes starch and polyol materials, and the mass ratio of starch and polyol materials is (1-2):1, such as 1:1, 1.5:1, 2:1, etc. The combination of the two is more conducive to improving the stability of the matrix material and improving the cycle performance of the final composite positive electrode material.
[0048] In some embodiments, the dopant containing the element M includes at least one of ammonium metavanadate, titanium dioxide, ammonium metavanadate, vanadium pentoxide, niobium pentoxide, anhydrous magnesium acetate, and magnesium oxide.
[0049] In some embodiments, the lithium source includes lithium phosphate.
[0050] In some embodiments, the anhydrous manganese ferrophosphate is prepared from a manganese ferrophosphate precursor (Mn 0.6 Fe 0.4 )3(PO4)2·6H2O is obtained by heat treatment; the heat treatment temperature is 500-600°C, for example, 500°C, 520°C, 550°C, 580°C or 600°C, etc., and the heat treatment time is 4-6h, for example, 4h, 4.5h, 5h, 5.5h or 6h, etc.
[0051] In some embodiments, the mixing speed is 200-600 rpm, such as 200 rpm, 250 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, and the mixing time is 10-30 min, such as 10 min, 15 min, 20 min, 25 min or 30 min. The present invention adopts appropriate mixing and stirring conditions to ensure that the materials are fully mixed.
[0052] In some embodiments, the mass of titanium nitride is 1% to 30% of the mass of the first material, for example 1%, 2%, 5%, 6%, 8%, 10%, 12%, 15%, 18%, 20%, 25% or 30%.
[0053] In some embodiments, in the titanium nitride dispersion, the solid content of titanium nitride is 5% to 30%, for example, 5%, 8%, 10%, 15%, 20%, 25% or 30%.
[0054] In some embodiments, the preparation of the titanium nitride dispersion specifically includes: subjecting a mixture of titanium nitride and water to high-pressure microfluidization; the pressure of the high-pressure microfluidization treatment is 10000-22000psi, such as 10000psi, 12000psi, 15000psi, 18000psi, 20000psi, 22000psi, etc., the flow rate of the high-pressure microfluidization treatment is 20-250mL / min, such as 10mL / min, 20mL / min, 30mL / min, 50mL / min, 80mL / min or 100mL / min, etc., and the time of the high-pressure microfluidization treatment is 30-60min, such as 30min, 40min, 50min or 60min, etc. The present invention adopts suitable high-pressure microfluidization treatment conditions to obtain a more uniformly dispersed titanium nitride dispersion, which is beneficial to the subsequent preparation of the coating layer and improves the comprehensive electrochemical performance of the composite positive electrode material.
[0055] In some embodiments, the mixing and stirring speed is 300-600 rpm, such as 300 rpm, 350 rpm, 400 rpm, 500 rpm, 600 rpm, etc. The mixing and stirring time is 30-70 min, such as 30 min, 40 min, 50 min, 60 min, etc. The present invention adopts appropriate mixing and stirring conditions to ensure that the titanium nitride dispersion and the first material are fully mixed to ensure the subsequent coating effect.
[0056] In some embodiments, the drying is carried out by spray drying, and the inlet air temperature of the spray drying is 150-250°C, for example, 150°C, 160°C, 180°C, 200°C, 250°C, etc. The pressure of the spray drying is 0.1-0.3MPa, for example, 0.1MPa, 0.2MPa, 0.3MPa, etc. The feed speed of the spray drying is 10-30rpm, for example, 10rpm, 20rpm or 30rpm, etc.
[0057] In some embodiments, the calcination includes a first constant temperature treatment and a second constant temperature treatment, the temperature of the first constant temperature treatment is 150-250°C, such as 150°C, 160°C, 180°C, 200°C, 220°C or 250°C, etc., the first constant temperature time is 3-6h, such as 3h, 3.5h, 4h, 5h or 6h, etc., the temperature of the second constant temperature treatment is 300-600°C, such as 300°C, 350°C, 400°C, 500°C or 600°C, etc., and the time of the second constant temperature treatment is 10-15h, such as 10h, 11h, 12h, 13h or 15h, etc. The calcination atmosphere is a protective gas, such as nitrogen, helium, etc. The heating rates of the first constant temperature treatment and the second constant temperature treatment are each independently 0.5-5°C / min.
[0058] In some embodiments, the calcination further includes screening.
[0059] According to another aspect of the present invention, the present invention also relates to a positive electrode sheet, comprising the composite positive electrode material, or the composite positive electrode material prepared by the method for preparing the composite positive electrode material.
[0060] The positive electrode sheet of the present invention has excellent electrochemical performance, and comprises a positive electrode current collector and a positive electrode layer arranged on at least one side surface of the positive electrode current collector, wherein the positive electrode layer contains the composite positive electrode material.
[0061] According to another aspect of the present invention, the present invention also relates to an aqueous zinc ion battery, comprising the positive electrode sheet described above.
[0062] The aqueous zinc ion battery of the present invention has excellent cycle stability.
[0063] The battery of the present invention also includes an electrolyte, which includes a soluble zinc salt, a soluble lithium salt and water, wherein the soluble zinc salt includes ZnSO4·7H2O, and the soluble lithium salt includes Li2SO4. The concentration of the soluble zinc salt is 0.7 to 1.2 mol / L, such as 0.7 mol / L, 0.9 mol / L, 1 mol / L, 1.2 mol / L, etc., and the concentration of the soluble lithium is 0.2 to 0.5 mol / L, such as 0.2 mol / L, 0.3 mol / L, 0.4 mol / L or 0.5 mol / L, etc.
[0064] The battery of the present invention adopts the composite positive electrode material and the electrolyte, Li + / Zn 2+ The dual carriers give it a higher energy density and voltage window. The composite cathode material with zinc metal anode has a higher output voltage of 1.8V, which is significantly higher than the traditional vanadium cathode material (VO2, V2O5) of 1.6V, and has a higher energy density potential.
[0065] In some embodiments, the method for preparing the electrolyte comprises: mixing a soluble zinc salt, a soluble lithium salt and water, the mixing speed is 100 to 300 rpm, such as 100 rpm, 150 rpm, 200 rpm, 250 rpm or 300 rpm, etc., and the mixing time is 10 to 30 min, such as 10 min, 15 min, 20 min or 25 min, etc. The method for preparing the electrolyte of the present invention can obtain a high-performance electrolyte.
[0066] According to another aspect of the present invention, the present invention also relates to an electrical device, comprising the aqueous zinc ion battery.
[0067] The following is further explained in conjunction with specific embodiments and comparative examples.
[0068] Example 1
[0069] A method for preparing a composite positive electrode material comprises the following steps:
[0070] (1) The manganese phosphate precursor (Mn 0.6 Fe 0.4 )3(PO4)2·6H2O is placed in a box furnace for sintering in a nitrogen atmosphere at a temperature of 500°C for 4 hours to obtain an anhydrous manganese ferrophosphate precursor.
[0071] (2) Weigh 500 g of the anhydrous ferromanganese phosphate obtained in step (1), add it to a stirring tank, add 317 g of lithium phosphate, then add 71.47 g of starch, 71.47 g of polyethylene glycol, 5.96 g of ammonium metavanadate and 2199 g of deionized water, stir for 25 min, and then grind in a sand mill to obtain material A.
[0072] (3) Titanium nitride was prepared into an aqueous solution with a solid content of 10%, and then dispersed under high pressure using a high-pressure microfluidizer. The equipment pressure was 20,000 psi and the flow rate was 200 mL / min. After the dispersion was completed, the solution was set aside for use and recorded as solution b.
[0073] (4) Material a and solution b were mixed, and after mixing, they were stirred at 500 rpm for 60 min using a stirrer. The prepared solution was recorded as solution c.
[0074] (5) The prepared solution c was spray dried, with a spray pressure of 0.2 MPa, an inlet air temperature of 200°C, and a feed speed (peristaltic speed) of 20 rpm.
[0075] (6) The spray-dried material was sieved with 400 mesh and then calcined in a tubular furnace at 200° C. for 5 h and 350° C. for 12 h, with a heating rate of 1° C. / min and a nitrogen atmosphere of 1 L / min.
[0076] (7) The calcined material is sieved through 400 meshes and then packaged to obtain a composite positive electrode material, wherein the mass content of TiN in the composite positive electrode material is 5%.
[0077] The scanning electron microscope image of the composite positive electrode material of this embodiment is as follows Figure 1 shown.
[0078] A method for preparing a battery comprises the following steps:
[0079] The composite positive electrode material, conductive carbon black and adhesive polyvinylidene fluoride (PVDF) of this embodiment are mixed in a mass ratio of 90:5:5, and N-methylpyrrolidone (NMP) is used as a solvent. After being adjusted into a slurry, it is evenly coated on an aluminum foil, dried at a suitable temperature, rolled to a desired thickness, and vacuum dried at 120°C for 12 hours to obtain a positive electrode sheet. The negative electrode uses a metal zinc foil, the diaphragm is a glass fiber diaphragm, and the electrolyte is 1mol / L ZnSO4+0.1mol Li2SO4. The preparation method of the electrolyte includes: dissolving 14.38g of ZnSO4·7H2O and 0.55g of Li2SO4 in 50mL of deionized water, stirring and mixing at a speed of 200rpm for 20min, and obtaining an aqueous zinc ion battery electrolyte, wherein the concentration of Li2SO4 is 0.1mol / L and the concentration of ZnSO4 is 1mol / L.
[0080] Example 2
[0081] A method for preparing a composite positive electrode material comprises the following steps:
[0082] (1) Manganese ferrophosphate precursor (Mn 0.6 Fe 0.4 )3(PO4)2·6H2O is placed in a box furnace for sintering in a nitrogen atmosphere at a temperature of 500°C for 4 hours to obtain an anhydrous manganese ferrophosphate precursor.
[0083] (2) Weigh 500 g of the anhydrous ferromanganese phosphate obtained in step 1, add it to a stirring tank, add 317 g of lithium phosphate, then add 71.47 g of starch, 71.47 g of polyethylene glycol, 5.96 g of ammonium metavanadate and 2199 g of deionized water, stir for 25 min, and then grind in a sand mill to obtain material a.
[0084] (3) Titanium nitride was prepared into an aqueous solution with a solid content of 7%, and then dispersed under high pressure using a high-pressure microfluidizer. The equipment pressure was 20,000 psi and the flow rate was 200 mL / min. After the dispersion was completed, the solution was set aside for use and recorded as solution b.
[0085] (4) Material a and solution b were mixed, and after mixing, they were stirred at 500 rpm for 60 min using a stirrer. The prepared solution was recorded as solution c.
[0086] (5) The prepared solution c was spray dried, with a spray pressure of 0.2 MPa, an inlet air temperature of 200°C, and a feed speed (peristaltic speed) of 20 rpm.
[0087] (6) The spray-dried material was sieved with 400 mesh and then calcined in a tubular furnace at 200° C. for 5 h and 350° C. for 12 h, with a heating rate of 1° C. / min and a nitrogen atmosphere of 1 L / min.
[0088] (7) The calcined material is sieved through 400 meshes and then packaged to obtain a composite positive electrode material, wherein the mass content of TiN in the composite positive electrode material is 7%.
[0089] The method for preparing a battery comprises the following steps:
[0090] The composite positive electrode material, conductive carbon black and adhesive polyvinylidene fluoride (PVDF) of this embodiment are mixed in a mass ratio of 90:5:5, and N-methylpyrrolidone (NMP) is used as a solvent. After being adjusted into a slurry, it is evenly coated on an aluminum foil, dried at a suitable temperature, rolled to a desired thickness, and vacuum dried at 120°C for 12 hours to obtain a positive electrode sheet. The negative electrode uses a metal zinc foil, the diaphragm is a glass fiber diaphragm, and the electrolyte is 1mol / L ZnSO4+0.1mol / L Li2SO4. The preparation method of the electrolyte includes: dissolving 14.38g ZnSO4·7H2O and 0.55g Li2SO4 in 50mL deionized water, and obtaining an aqueous zinc ion battery electrolyte at a speed of 200rpm, wherein the concentration of Li2SO4 is 0.1mol / L and the concentration of ZnSO4 is 1mol / L.
[0091] Example 3
[0092] A method for preparing a composite positive electrode material comprises the following steps:
[0093] (1) Manganese ferrophosphate precursor (Mn 0.6 Fe 0.4 )3(PO4)2·6H2O is placed in a box furnace for sintering in a nitrogen atmosphere at a temperature of 500°C for 4 hours to obtain an anhydrous manganese ferrophosphate precursor.
[0094] (2) Weigh 500 g of the anhydrous ferromanganese phosphate obtained in step 1, add it to a stirring tank, add 317 g of lithium phosphate, then add 71.47 g of starch, 71.47 g of polyethylene glycol, 5.96 g of ammonium metavanadate and 2199 g of deionized water, stir for 25 min, and then grind in a sand mill to obtain material a.
[0095] (3) Titanium nitride was prepared into an aqueous solution with a solid content of 5%, and then dispersed under high pressure using a high-pressure microfluidizer. The equipment pressure was 20,000 psi and the flow rate was 200 mL / min. After the dispersion was completed, the solution was set aside for use and recorded as solution b.
[0096] (4) Material a and solution b were mixed, and after mixing, they were stirred at 500 rpm for 60 min using a stirrer. The prepared solution was recorded as solution c.
[0097] (5) The prepared solution C was spray dried with a spray pressure of 0.2 MPa, an inlet air temperature of 200°C, and a feed speed (peristaltic speed) of 20 rpm.
[0098] (6) The spray-dried material was sieved with 400 mesh and then calcined in a tubular furnace at 200° C. for 5 h and 350° C. for 12 h, with a heating rate of 1° C. / min and a nitrogen atmosphere of 1 L / min.
[0099] (7) The calcined material is sieved through 400 meshes and then packaged to obtain a composite positive electrode material, wherein the mass content of TiN in the composite positive electrode material is 5%.
[0100] The method for preparing a battery comprises the following steps:
[0101] The composite positive electrode material, conductive carbon black and adhesive polyvinylidene fluoride (PVDF) of this embodiment are mixed in a mass ratio of 90:5:5, and N-methylpyrrolidone (NMP) is used as a solvent. After being adjusted into a slurry, it is evenly coated on an aluminum foil, dried at a suitable temperature, rolled to a desired thickness, and vacuum dried at 120°C for 12 hours to obtain a positive electrode sheet. The negative electrode uses a metal zinc foil, the diaphragm is a glass fiber diaphragm, and the electrolyte is 1mol / L ZnSO4+0.5mol Li2SO4. The preparation method of the electrolyte includes: dissolving 14.38g ZnSO4·7H2O and 0.55g Li2SO4 in 50mL deionized water, stirring and mixing at a speed of 200rpm for 20min, and obtaining an aqueous zinc ion battery electrolyte, wherein the concentration of Li2SO4 is 0.1mol / L and the concentration of ZnSO4 is 1mol / L.
[0102] Example 4
[0103] The preparation method of the composite positive electrode material is the same as that of Example 1.
[0104] The preparation method of the battery is different from that of Example 1 in that the electrolyte is 0.2mol / LZnSO4+0.9molLi2SO4, 12.51g ZnSO4·7H2O and 1.1g Li2SO4 are dissolved in 50mL deionized water, and stirred and mixed at a speed of 200rpm for 20min to obtain an aqueous zinc ion battery electrolyte, wherein the concentration of Li2SO4 is 0.2mol / L and the concentration of ZnSO4 is 0.9mol / L.
[0105] Example 5
[0106] The preparation method of the composite positive electrode material is the same as that of Example 1.
[0107] The preparation method of the battery is different from that of Example 1 in that the electrolyte is 0.4 mol / LLi2SO4+0.7 mol / LZnSO4. The preparation method of the electrolyte comprises: dissolving 9.73 g ZnSO4·7H2O and 2.2 g Li2SO4 in 50 mL deionized water, stirring and mixing at a speed of 200 rpm for 20 min, and obtaining an aqueous zinc ion battery electrolyte, wherein the concentration of Li2SO4 is 0.4 mol / L, and the concentration of ZnSO4 is 0.7 mol / L.
[0108] Example 6
[0109] A method for preparing a composite positive electrode material comprises the following steps:
[0110] (1) Manganese ferrophosphate precursor (Mn 0.6 Fe 0.4 )3(PO4)2·6H2O is placed in a box furnace for sintering in a nitrogen atmosphere at a temperature of 400°C for 6 hours to obtain an anhydrous manganese ferrophosphate precursor.
[0111] (2) Weigh 500 g of the anhydrous ferromanganese phosphate obtained in step 1, add it to a stirring tank, add 317 g of lithium phosphate, then add 80 g of maltose, 80 g of polyvinyl alcohol, 5.32 g of niobium pentoxide and 2300 g of deionized water in sequence, stir for 20 min, and then grind in a sand mill to obtain material a.
[0112] (3) Titanium nitride was prepared into an aqueous solution with a solid content of 7%, and then dispersed under high pressure using a high-pressure microfluidizer with a pressure of 15,000 psi and a flow rate of 80 mL / min. After the dispersion was completed, the solution was set aside for use and recorded as solution b.
[0113] (4) Material a and solution b were mixed, and after mixing, they were stirred at 600 rpm for 45 min. The prepared solution was recorded as solution c.
[0114] (5) The prepared solution c was spray dried, with a spray pressure of 0.3 MPa, an inlet air temperature of 250°C, and a feed speed (peristaltic speed) of 20 rpm.
[0115] (6) The spray-dried material was sieved with 400 mesh and then calcined in a tubular furnace at 150° C. for 6 h and 500° C. for 5 h, with a heating rate of 2° C. / min and a nitrogen atmosphere of 1 L / min.
[0116] (7) The calcined material is sieved with 400 meshes, and then packaged to obtain a composite positive electrode material, wherein the mass content of TiN in the composite positive electrode material is 10%.
[0117] A method for preparing a battery, except that the composite positive electrode material in this embodiment is used, other conditions are the same as those in Example 1.
[0118] Example 7
[0119] A method for preparing a composite positive electrode material comprises the following steps:
[0120] (1) Manganese ferrophosphate precursor (Mn 0.6 Fe 0.4 )3(PO4)2·6H2O is placed in a box furnace for sintering in a nitrogen atmosphere at a temperature of 600°C for 4 hours to obtain an anhydrous manganese ferrophosphate precursor.
[0121] (2) Weigh 500 g of the anhydrous ferromanganese phosphate obtained in step 1, add it to a stirring tank, add 317 g of lithium phosphate, then add 90 g of sucrose, 45 g of polyethylene glycol, 5.46 g of vanadium pentoxide and 2250 g of deionized water, stir for 20 min, and then grind in a sand mill to obtain material a.
[0122] (3) Titanium nitride was prepared into an aqueous solution with a solid content of 7%, and then dispersed under high pressure using a high-pressure microfluidizer. The equipment pressure was 10,000 psi and the flow rate was 100 mL / min. After the dispersion was completed, the solution was set aside for use and recorded as solution b.
[0123] (4) Material a and solution b were mixed, and after mixing, agitated at 450 rpm for 60 min. The prepared solution was recorded as solution c.
[0124] (5) The prepared solution c was spray dried, with a spray pressure of 0.1 MPa, an air inlet temperature of 150°C, and a feed speed (peristaltic speed) of 30 rpm.
[0125] (6) The spray-dried material was sieved with 400 mesh and then calcined in a tubular furnace at 250° C. for 3 h and 400° C. for 13 h, with a heating rate of 1° C. / min and a nitrogen atmosphere of 1 L / min.
[0126] (7) The calcined material is sieved with 400 meshes and then packaged to obtain a composite positive electrode material, wherein the mass content of TiN in the composite positive electrode material is 12%.
[0127] A method for preparing a battery, except that the composite positive electrode material in this embodiment is used, other conditions are the same as those in Example 1.
[0128] Comparative Example 1
[0129] A method for preparing a positive electrode material comprises the following steps:
[0130] (1) Manganese ferrophosphate precursor (Mn 0.6 Fe 0.4 )3(PO4)2·6H2O is placed in a box furnace for sintering in a nitrogen atmosphere at a temperature of 500°C for 4 hours to obtain an anhydrous manganese ferrophosphate precursor.
[0131] (2) Weigh 500 g of the anhydrous ferromanganese phosphate obtained in step 1, add it to a stirring tank, add 317 g of lithium phosphate, then add 71.47 g of starch, 71.47 g of polyethylene glycol, 5.96 g of ammonium metavanadate and 2199 g of deionized water, stir for 25 min, and then grind in a sand mill to obtain material a.
[0132] (3) The prepared C solution was spray dried at a spray pressure of 0.2 MPa, an inlet air temperature of 200° C., and a feed speed (peristaltic speed) of 20 rpm.
[0133] (4) The spray-dried material was sieved with 400 mesh and then calcined in a tubular furnace at 200° C. for 5 h and 350° C. for 12 h, with a heating rate of 1° C. / min and a nitrogen atmosphere of 1 L / min.
[0134] (5) The calcined material was sieved through 400 mesh and then packaged to obtain the finished product sample LiFe 0.4 Mn 0.6 PO 4。
[0135] The preparation method of the battery is the same as that of Example 1 except that the composite positive electrode material in this comparative example is used.
[0136] Comparative Example 2
[0137] The preparation method of the battery is different from that of Example 1 in that the electrolyte is 1 mol / L ZnSO4, and the preparation method of the electrolyte comprises: dissolving 14.35 g ZnSO4·7H2O in 50 mL deionized water, stirring and mixing at a speed of 200 rpm for 20 min to obtain an aqueous zinc ion battery electrolyte, wherein the concentration of ZnSO4 is 1 mol / L.
[0138] Experimental example
[0139] The batteries obtained in the examples and comparative examples were subjected to electrochemical performance tests, and the results are shown in Table 1. Initial specific capacity test conditions: 1C, 0V-1.8V test, 1C=300mAh / g.
[0140] Table 1 Electrochemical performance test results of the battery
[0141]
[0142]
[0143] As shown in Table 1, the battery obtained by combining the composite positive electrode material of the present invention with the electrolyte has a Li + / Zn 2+ The dual carriers give it a higher energy density and voltage window. The first efficiency of the battery is greater than or equal to 80.9%, and the capacity retention rate after 100 cycles is above 88%.
[0144] In Comparative Example 1, the surface of the positive electrode material is not coated with titanium nitride, and the obtained battery has a low initial efficiency and a low capacity retention rate after 100 cycles.
[0145] In Comparative Example 2, the electrolyte is 1 mol / L ZnSO4, the capacity of the obtained battery is reduced, and the first efficiency and cycle performance are significantly reduced.
[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite positive electrode material, characterized in that: It includes a positive electrode substrate and a coating layer coated on the surface of the positive electrode substrate; The positive electrode substrate includes a core material and a carbon material layer coated on the surface of the core material, the core material includes lithium manganese iron phosphate material and a doping element M, and the doping element M includes at least one of vanadium, titanium, niobium and magnesium; The coating layer includes titanium nitride.
2. The composite positive electrode material according to claim 1, characterized in that The mass of the coating layer is 2% to 20% of the mass of the composite positive electrode material.
3. The method for preparing a composite positive electrode material according to claim 1 or 2, characterized in that: The following steps are involved: Anhydrous manganese ferrophosphate, a lithium source, a carbon source, a dopant containing element M and a solvent are mixed and ground to obtain a first material; a dispersion of titanium nitride and the first material are mixed and stirred, and then dried and calcined.
4. The method for preparing a composite positive electrode material according to claim 3, characterized in that: Contains at least one of the following features (1) to (4): (1) The mass ratio of the anhydrous manganese ferrophosphate, the lithium source, the carbon source, the dopant containing the element M and the solvent is (300-600):(200-350):(120-200):(4-8):(1800-2500); (2) the carbon source comprises at least one of starch, sucrose, fructose, maltose, cyclodextrin, citric acid and polyol materials; (3) the dopant containing the element M comprises at least one of ammonium metavanadate, titanium dioxide, ammonium metavanadate, vanadium pentoxide, niobium pentoxide, anhydrous magnesium acetate and magnesium oxide; (4) The lithium source includes lithium phosphate.
5. The method for preparing a composite positive electrode material according to claim 3, characterized in that: Contains at least one of the following features (1) to (8): (1) The anhydrous ferromanganese phosphate is obtained by heat treating a ferromanganese phosphate precursor; the heat treatment temperature is 500 to 600° C., and the heat treatment time is 4 to 6 hours; (2) The mixing process is performed at a rotation speed of 200 to 600 rpm and a mixing process time of 10 to 30 min; (3) The mass of the titanium nitride is 1% to 30% of the mass of the first material; (4) In the titanium nitride dispersion, the solid content of titanium nitride is 5% to 30%; (5) The preparation of the titanium nitride dispersion specifically comprises: subjecting a mixture of titanium nitride and water to high-pressure microfluidization treatment; The pressure of the high-pressure microfluidization treatment is 10000-22000 psi, the flow rate of the high-pressure microfluidization treatment is 20-250 mL / min, and the time of the high-pressure microfluidization treatment is 30-60 min; (6) The mixing speed is 300 to 600 rpm, and the mixing time is 30 to 70 min; (7) The drying is carried out by spray drying, the air inlet temperature of the spray drying is 150 to 250° C., the pressure of the spray drying is 0.1 to 0.3 MPa, and the feed speed of the spray drying is 10 to 30 rpm; (8) The calcination includes a first constant temperature treatment and a second constant temperature treatment, wherein the temperature of the first constant temperature treatment is 150-250°C, the first constant temperature treatment time is 3-6 hours, the temperature of the second constant temperature treatment is 300-600°C, and the second constant temperature treatment time is 10-15 hours.
6. A positive electrode sheet, characterized in that: The invention comprises the composite positive electrode material according to claim 1 or 2, or a composite positive electrode material prepared by the method for preparing a composite positive electrode material according to any one of claims 3 to 5.
7. An aqueous zinc ion battery, characterized in that: Including the positive electrode sheet as described in claim 6.
8. The aqueous zinc ion battery according to claim 7, characterized in that: The battery also includes an electrolyte, which includes a soluble zinc salt, a soluble lithium salt and water. The soluble zinc salt includes ZnSO4·7H2O, the soluble lithium salt includes Li2SO4, the concentration of the soluble zinc salt is 0.7-1.2 mol / L, and the concentration of the soluble lithium is 0.2-0.5 mol / L.
9. The aqueous zinc ion battery according to claim 8, characterized in that: The preparation method of the electrolyte comprises: mixing a soluble zinc salt, a soluble lithium salt and water at a mixing speed of 100 to 300 rpm for 10 to 30 minutes.
10. An electrical device, characterized in that: An aqueous zinc ion battery comprising the aqueous zinc ion battery according to any one of claims 7 to 9.
Citation Information
Patent Citations
Anode material made through element microemulsion coating method, manufacturing method and application
CN104143633A
Aqueous zinc ion battery and preparation method of positive electrode material thereof
CN110828800A
Aqueous mixed ion secondary battery, preparation method and application thereof
CN112259722A
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN114477300A
Ternary positive electrode material, preparation method and application thereof
CN116247210A